2020
DOI: 10.1021/acsnano.9b09993
|View full text |Cite
|
Sign up to set email alerts
|

Inelastic Light Scattering by Long Narrow Gold Nanocrystals: When Size, Shape, Crystallinity, and Assembly Matter

Abstract: We report the synthesis of long narrow gold nanocrystals and the study of their vibrational dynamics using inelastic light scattering measurements. Rich experimental spectra 1 are obtained for monodomain gold nanorods and pentagonal twinned bipyramids. Their assignment involves diameter-dependent non-totally symmetric vibrations which are modeled in the framework of continuum elasticity by taking into account simultaneously the size, shape and crystallinity of the nanocrystals. Light scattering by vibrations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 47 publications
(128 reference statements)
0
21
0
Order By: Relevance
“…For a single Au NR, the fundamental extensional mode is the BLS active mode of the lowest frequency. The appearance of spectral peaks below the fundamental extensional frequency can result from the vibrational and plasmonic coupling of aggregated nanostructures. The BLS peaks above the fundamental extensional frequency are contributed by either the trivial polymer matrix and glass substrate or various normal modes of Au NRs to be assigned by theoretical simulations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For a single Au NR, the fundamental extensional mode is the BLS active mode of the lowest frequency. The appearance of spectral peaks below the fundamental extensional frequency can result from the vibrational and plasmonic coupling of aggregated nanostructures. The BLS peaks above the fundamental extensional frequency are contributed by either the trivial polymer matrix and glass substrate or various normal modes of Au NRs to be assigned by theoretical simulations.…”
Section: Resultsmentioning
confidence: 99%
“…(4) Normal Au NR modes with frequency f > f normale normalx normalt ( n = 0 ) are clearly resolved in the spectrum of Au700 recorded with 532 nm (Figure a). Focusing on this spectrum with the richest structure and the most well-separated peaks, the quadrupolar mode, which is mainly determined by NR diameter, is BLS active and appears at ∼20 GHz. Experimentally, this BLS peak is better represented by a double Lorentzian (∼17 and 20 GHz), and it can contain a contribution from the bulk phonons in PVA or multiple Au NR modes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent decades, solution-processed colloidal gold nanoparticles, especially gold nanorods (Au NRs), have aroused extensive interest in the application of photosensing and optoelectronic devices owing to their attractive properties: (i) the dominant optical properties of surface plasmon resonance (SPR), (ii) the tunability of the nanorod aspect-ratio and the resultant tunable optical extinction, (iii) high physical and chemical stability and low biological toxicity. [1][2][3][4][5][6] Due to these fascinating properties, a great deal of research and literature have emerged on Au NRs synthesis, [7][8][9] selfassembling, [10][11][12] light scattering, [13,14] photoluminescence, [15,16] coupling modes. [17][18][19] Meanwhile, vast amounts of applications of colloidal Au NRs emerged in photocatalysis, [20,21] in photovoltaics, [22] in photodetectors, [23][24][25][26] and in biomedical fields (such as vivo imaging [27][28][29] and photothermal cancer therapy).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] These techniques typically allow the detection of one or a few nano-object modes with frequencies in the GHz-THz range, of the order of the ratio between sound velocity and nano-object size. The experimental and theoretical investigations performed in the last twenty years have largely clarified the dependence of the vibrational frequencies of isolated nano-objects on their size, shape and elastic properties, [7][8][9][10][11][12] and shown that they are usually reliably predicted by continuum mechanics approaches for nano-objects with sizes down to 1 nm, without having to consider a sizeinduced modification of their elastic constants. 4,5,[13][14][15][16] In this context, the interest of nanoacoustics researchers is now shifting to less understood aspects of the vibrational response of nano-objects, including in particular damping and coupling phenomena, the latter constituting the scope of this paper.…”
Section: Introductionmentioning
confidence: 99%